2014
DOI: 10.4161/cbt.29171
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab-induced recruitment of Csk-homologous kinase (CHK) to ErbB2 receptor is associated with ErbB2-Y1248 phosphorylation and ErbB2 degradation to mediate cell growth inhibition

Abstract: The inhibitory effect of trastuzumab, a humanized monoclonal antibody directed against the extracellular domain of ErbB2, is associated with its ability to induce ErbB2-Y1248 phosphorylation, and the status of phosphorylated ErbB2-Y1248 (ErbB2-pY1248) may correlate with the sensitivity of breast cancers to trastuzumab. The mechanisms of which remain unclear. Here, we show that binding of trastuzumab to ErbB2 activates ErbB2 kinase activity and enhances ErbB2-Y1248 phosphorylation in trastuzumab-sensitive breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 39 publications
7
54
0
Order By: Relevance
“…Negative signals downstream of ERBB2 subsequently contribute to growth inhibition of ERBB2-positive breast cancer cells. 9,10 Taken together, these studies provide evidence that trastuzumab does not function as a TKI. …”
Section: Nishant Mohan and Wen Jin Wumentioning
confidence: 89%
See 4 more Smart Citations
“…Negative signals downstream of ERBB2 subsequently contribute to growth inhibition of ERBB2-positive breast cancer cells. 9,10 Taken together, these studies provide evidence that trastuzumab does not function as a TKI. …”
Section: Nishant Mohan and Wen Jin Wumentioning
confidence: 89%
“…7 Gijsen and co-workers also reported that trastuzumab induced ERBB2 tyrosine phosphorylation, 8 and together with another group observed that trastuzumab treatment induced paradoxical activation of mitogenactivated protein kinase 1/3 in breast cancer cells. 8,9 In 2014, we demonstrated that trastuzumab upregulated ERBB2 tyrosine kinase activity in trastuzumab-sensitive breast cancer cells, and that this upregulated a ctivity contributed to ERBB2 phosphorylation. 9 Despite different effects on ERBB2 phosphorylation, both lapatinib and trastuzumab have the capacity to downregulate Akt activity and to inhibit growth of breast cancer cells.…”
Section: Nishant Mohan and Wen Jin Wumentioning
confidence: 94%
See 3 more Smart Citations